1997
DOI: 10.1002/ardp.19973300802
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Investigations of Pyrimidine Derivatives

Abstract: The study concerns new syntheses of 5-hydroxy ether and 5-aminohydroxy ether derivatives of pyrimidine. When tested for antibacterial activity, some of the compounds exhibited promising effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Pyrimidine derivatives have been reported as anti-microbial [3], analgesic, anti-viral, anti-inflammatory [4], anti-HIV [5], anti-tubercular [6], anti-tumour [7], anti-malarial [8], cardiovascular [9] agents. Pyrimidine derivatives have been found to exhibit cytostatic [10][11][12], immune modulating [13,14] and antibacterial properties [15][16][17][18][19][20][21]. In particular, studies concerning the synthesis of pyrimido [4,5-d]-1,3-oxazines [22] showing considerable similarity to quinoline chemotherapeutic agents with an antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidine derivatives have been reported as anti-microbial [3], analgesic, anti-viral, anti-inflammatory [4], anti-HIV [5], anti-tubercular [6], anti-tumour [7], anti-malarial [8], cardiovascular [9] agents. Pyrimidine derivatives have been found to exhibit cytostatic [10][11][12], immune modulating [13,14] and antibacterial properties [15][16][17][18][19][20][21]. In particular, studies concerning the synthesis of pyrimido [4,5-d]-1,3-oxazines [22] showing considerable similarity to quinoline chemotherapeutic agents with an antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…Results of previous research on synthesis and biological properties of pyrimidine ring have demonstrated that the system is capable of extremely potent biological activity. The obtained derivatives revealed both cytostatic [1,2], immunomodulating [3,4] and first of all antibacterial [5,6,7] properties. That is why we found usefbl to carry out a number of syntheses aiming at obtaining 5-substituted pyrimidine sulphonamides.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial studies on the Schiff and Mannich bases of isatin and its derivatives with pyrimidine analogues were considered important from the fact that pyrimidine compounds have shown antibacterial [94,95], antifungal [96], antimycobacterial [97] and HIV RT inhibitory [98,99] properties. The N-Mannich bases of 3-[4'-(4"-chlorophenyl)-6'-(4"'-methylphenyl) pyrimidin-2'-yl] imino isatin were synthesized and their antibacterial, antifungal, antitubercular and anti-HIV activities were carried out.…”
Section: Isatinimino Compounds a Potential Lead For The Effective Trmentioning
confidence: 99%